Foreign Investments of American Coporations - Epstein, Ralph C. (The Review of Economics and Statistics, 1952)
to encourage international commerce make it important to have such knowledge currently. The writer, in Novemnber i95o, requested information on their foreign holdings from more than a hundred American manufacturing corporations.2 Seventy-two companies supplied the data which are summarized in Table i. As of May I943, the Treasury study showed the foreign assets of American corporations and individuals with a 25 per cent interest or more in companies abroad, as amounting to $7,365,000,ooo. About 6,ooo corporations and indi-